(untitled) (Bangladesh Heart Journal, 2018)
Objective: The objective of the present study was to provide recent population-based information on use of cardiovascular drugs in outpatients in a tertiary care hospital of Dhaka, Bangladesh. Methods: A prospective study of cardiovascular prescriptions of Outpatient Department of Department of Cardiology of Shaheed Suhrawardy Medical college hospital Dhaka, Bangladesh was carried out. A total of 215 prescriptions were collected for the study in Shaheed Suhrawardy Medical College Hospital Dhaka, Bangladesh from July 2015 to June 2016. The prescriptions were evaluated for rationality based on WHO model list of essential medicines. The prescriptions were critically analyzed using predetermined parameters. Results: Out of 215 prescriptions collected, 120 drugs were found to be repeatedly prescribed. The results revealed that all single dose formulations prescribed were rationally in accordance with WHO essential drug list whereas fixed dose combinations prescribed remain questionable. A pattern of polypharmacy was clearly evident. Conclusion: Medications are a critical modality for prolongation and improved quality of life. Campaign and intervention should be focused on patients with more than three diagnostic cardiovascular conditions in order to minimize polypharmacy in patients particularly elderly. Bangladesh Heart Journal 2017; 32(2) : 65-69